Botanical and geographical origins of honey samples from Pantanal (Mato Grosso and Mato Grosso do Sul states, Brazil) certificated by melissopalynology. Issue 3 (4th May 2021) - da Luz, Cynthia Fernandes Pinto; Chaves, Sérgio Augusto de Miranda; Cano, Cristiane Bonaldi
Abstract: Twenty honey samples of Apis mellifera were collected during the main flowering period (July–October) between 2003 and 2018. Six apiaries in Mato Grosso (MT) state and three apiaries in Mato Grosso do Sul (MS) state were sampled. The vegetation in the region is non-flooding, seasonally flooded and aquatic savanna with scattered forested patches (seasonal semi-deciduous forest, Cerrado and Cerradão). Samples were analysed by non-acetolysed method in order to understand the relative pollen frequencies. A principal component analysis (PCA) was used to compare the similarity between the samples. Within the 13 MT honey samples, 63 pollen types from 55 genera and 40 families were identified, as well as three undetermined pollen types. Monofloral MT honey of Curatella americana ('lixeira') and Myracrodruon urundeva ('aroeira') were recognised. In the seven MS honey samples, a total of 40 pollen types from 32 genera and 24 families were identified. Monofloral MS honey included Myracrodruon urundeva, Stryphnodendron adstringens ('barbatimão') and Richardia ('bernarda'). The results of the analyses did not correspond to the flowering sources declared by the beekeepers. To ensure the palynological differentiation of Pantanal honey required by international trade as PGI (Protected Geographical Indication), a greater control over its botanical origin is necessary, through melissopalynological analysis.